2013
DOI: 10.3402/polar.v32i0.17309
|View full text |Cite
|
Sign up to set email alerts
|

Electrical structure beneath Schirmacher Oasis, East Antarctica: a magnetotelluric study

Abstract: Maitri Station (70.76°S; 11.73°E) is located in Schirmacher Oasis, a coastal nunatak in north-central Dronning Maud Land covering an area of 35 km2. Here, we report results from the first magnetotelluric experiments and delineate the deep electrical conductivity structure under Schirmacher Oasis using the data acquired during the 24th Indian Antarctic Scientific Expedition. The magnetotelluric method has the advantage of shallow to deeper level coverage as the data acquisition covers a wide frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Thick ice covers nearly all of Antarctica; thus, geophysical methods are required to image sub‐ice geological structures. Magnetotellurics (MT) is a passive electromagnetic method that is an important geophysical technique for investigating sub‐ice structure in Antarctica as it combines good resolution, minimal environmental impact, and favorable logistics [e.g., Beblo and Liebig , ; Wannamaker et al , ; Murthy et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Thick ice covers nearly all of Antarctica; thus, geophysical methods are required to image sub‐ice geological structures. Magnetotellurics (MT) is a passive electromagnetic method that is an important geophysical technique for investigating sub‐ice structure in Antarctica as it combines good resolution, minimal environmental impact, and favorable logistics [e.g., Beblo and Liebig , ; Wannamaker et al , ; Murthy et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, they also collected high-quality MT data onto the eastern Antarctica, which proved the feasibility of MT data collection of the whole Antarctic region (Wannamaker et al, 2004). After that, Armadillo et al (2004), Murthy et al (2013), Peacock and Selway (2016) also showed the excellent MT measurement at the eastern Antarctica (Figure 1). Long-period magnetotelluric (LMT) can be used to study the electrical structure of earth crust and mantle (Lizarralde et al, 1995;Mackie et al, 1988;Unsworth et al, 2005).…”
Section: Introductionmentioning
confidence: 79%
“…However, due to the fact that Antarctica is covered by ice and snow, limited by the bad natural environment and logistics supply difficulties, it is relatively difficult to carry out largescale long-time MT measurement continuously. At present, the most detection depth is generally within 40 kms using MT method (Armadillo et al, 2004;Murthy et al, 2013;Peacock and Selway, 2016;Wannamaker et al, 2004). The geophysical research on the structure of the Antarctic plate crust and lithospheric mantle is still focused on imaging the broadband seismic base station data (An et al, 2015;Heeszel et al, 2016;Ritzwoller et al, 2001), processing and inversion of satellite gravity anomaly data (Haeger et al, 2019;Ji et al, 2018;Scheinert et al, 2016), and joint processing and interpretation based on gravity and seismic data (Baranov et al, 2017;Tenzer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Surface wave studies found craton-like velocities in East Antarctica (Bentley 1991;Ritzwoller et al 2001). A deep electrical conductivity structure under Schirmacher Oasis in central DML showed highly resistive (8000-10 000 ohm m) upper crust followed by lesser resistive (500-600 ohm m) lower crust; and the results were interpreted that the Schirmacher Oasis to be a stable cratonic platform (Murthy et al 2013). Another magnetotelluric study in the Schirmacher Oasis ( Fig.…”
Section: Introductionmentioning
confidence: 91%